Identification and Analysis of Melon (Cucumis melo L.) SHMT Gene Family Members and Their Functional Studies on Tolerance to Low-Temperature Stress - Yanmin Liu; Dandan He; Yizhou Wu; Kangqi Zhao; Changyi Yang; Yulu Zhong; Liuyang Yang; Haiyue Niu; Sushuang Liu (Agronomy)
Melon (Cucumis melo L.) is a significant cash crop globally and is cherished for its sweet and flavorful fruits, as well as its high nutritional values. However, its yield and quality are limited by various factors, including drought, salinity, and low temperatures. Low temperatures are one of the primary factors influencing the growth and development of melons, diminishing the viability, germination, and growth rate of melon seeds. Concurrently, low temperatures also reduce light absorption efficiency and fruit yields, thereby affecting melon growth and development. Serine hydroxymethyltransferase (SHMT), a conserved phosphopyridoxal-dependent enzyme, plays a crucial role in plant resistance to abiotic stressors. In this study, eight CmSHMT family genes were identified from the melon genome. We predicted their chromosomal locations, physicochemical properties, gene structures, evolutionary relationships, conserved motifs, cis-acting elements of promoters, and tissue-specific expression patterns. The expression levels of CmSHMT family genes in response to low-temperature stress was then analyzd using qRT-PCR. The phylogenetic results indicated that these CmSHMT genes were classified into four subfamilies and were unevenly distributed across five chromosomes, with relatively high conservation among them. Furthermore, our investigation revealed that the promoter regions of the CmSHMT family genes contain many cis-acting elements related to phytohormones, growth, and various stress responses. The relative expression levels of CmSHMT3, CmSHMT4, CmSHMT6, and CmSHMT7 were higher under low-temperature stress compared to the control group. Notably, the promoter region of CmSHMT3 contains cis-acting elements associated with low-temperature response (LTR) and abscisic acid response (ABRE). It is suggested that the mechanism through which CmSHMT3 responds to low-temperature stress treatments may be associated with hormonal regulation. These findings provide a foundation for the further exploration of CmSHMT family genes in melon and their functional roles in response to low-temperature stress, and they provide a theoretical basis for the targeted breeding of superior melon varieties with enhanced tolerance to low temperatures.